Normalizing Psychological Pressure in Hustle Culture: Transforming Work Identity and Pursuing Constant Productivity in the Digital Economy - Cita Silvastiani (Jurnal Community, 2025)
This study analyzes how the normalization of productivity pressure in hustle culture is shaped through the glorification of non-stop work, the internalization of the neoliberal ethos of self-optimization, and the construction of identities based on digital performativity in the platform economy ecosystem. Using a qualitative approach through digital ethnography and critical discourse analysis (CDA), this study examines media representations, digital motivational content, displayed productivity practices, and assessment mechanisms in gig platforms using naturally occurring data from international media, social media, and other digital materials. The findings of this study show that extreme productivity is positioned as a new moral standard, indicating that individuals are encouraged to manage risk, self-discipline, and work performance as personal responsibilities. This study concludes that the professional identity of the younger generation is shaped through the visualization of work activities, platform ratings, and comparative narratives that link self-worth to displayed performance. This study provides a theoretical contribution by formulating a framework on the relationship between the discourse of productivity, internalization processes, and the performativity of identity in the digital economy, as well as offering practical implications for policy design and a more sustainable work ecosystem to reduce culturally legitimized productivity pressures